Italian prison system facing coronavirus: between troubles and resilience - Carlotta Vignali (Firenze University Press, 2021)
This contribution is an analysis on the consequences of the coronavirus spread in the Italian prison system, highlighting concerns and potential prospects of improvements. Like other extremely vulnerable contexts, prisons are affected by the spread of Covid-19, resulting however weaker in providing effective strategies to ensure prevention, health and safety. Due to structural flaws, unhealthy conditions and endemic shortfalls, penitentiaries see a high risk of an outbreak of the illness. The prison crumbling and chronic overcrowded state make social distancing impossible. In addition to this, the coronavirus impact exacerbates pre-existing difficulties of the prison system. In such a dramatic scenario, and in spite of the inadequate government response in providing efficient resources against the virus diffusion, some detention facilities seem to be resilient in fighting back the epidemic, adopting strategies and solutions which could be considered a valuable starting point towards a better way of conceiving punishment.   Il carcere italiano di fronte al coronavirus: tra criticità e resilienza.   Il contributo presenta un'analisi circa le ripercussioni della diffusione del coronavirus nel sistema penitenziario, mettendo in luce le criticità e le potenziali prospettive di miglioramento. Il carcere, come tutti gli altri contesti contraddistinti da un elevato grado di vulnerabilità, non è immune rispetto alla diffusione del Covid-19, ma si dimostra debole nel garantire efficaci strategie di prevenzione e sicurezza sanitaria. A causa delle carenze strutturali, dell'insalubrità e dei deficit endemici degli istituti di pena, appare concreto il rischio che i luoghi di detenzione si trasformino in vivi focolai di malattia. Le fatiscenti condizioni dei penitenziari e la cronica condizione di sovraffollamento rendono impraticabile il distanziamento sociale e, al tempo stesso, l'impatto del coronavirus esaspera i nodi critici preesistenti all'interno dei circuiti penitenziari. In questo drammatico scenario, per quanto i provvedimenti adottati dal governo risultino insufficienti nel fornire gli strumenti adeguati al contrasto della diffusione del virus, alcune strutture si mostrano resilienti nel fronteggiare l'epidemia, mettendo in pratica una serie di strategie e soluzioni che possono costituire un valido punto di partenza verso un modo migliore di intendere la pena.